The category management handbook - Cordell, Andrea, 1965-; Thompson, Ian, 1967- (Routledge, 2018)
Category management is one of the biggest contributors of commercial value in the area of procurement and supply chain. With a proven track record of successful delivery since the early 1990s, it helps organisations gather and analyse key data about their procurement spend before subsequently creating and delivering value-adding strategies that change the value proposition from supply chains. The aim of category management is to find long-term breakthrough strategies that help lift an organisation's commercial performance to a new level. Because of its strategic long-term orientation and complex execution, category management has long been the preserve of commercial consulting companies - in effect a 'black box' toolkit shrouded in expensive methodologies. This practical handbook lifts the lid on category management by providing readers with a step-by-step process and established toolkit that allows them a 'do-it-yourself' approach. Each activity is presented as a simple tool or technique for practitioners to apply to their own organisations. To support each activity, easy-to- use templates and checklists have been provided, together with simple but practical hints and tips for implementation. This handbook is a 'must read' for all procurement and supplychain managers looking to find significant improvements in their organisations. Its practical approach cuts through long-winded consultant-speak and provides an easy-to-use practical toolkit for everyday application.